Safety of Trypan Blue Capsule Staining to Corneal Endothelium in Patients with Diabetic Retinopathy - Hazem Abdelmotaal; Khaled Abdelazeem; Mohamed S. Hussein; Ahmed F. Omar; Walid Ibrahim (Journal of Ophthalmology, 2019)
Purpose. To study the potential corneal endothelial cell toxicity of trypan blue (TB) when used for phacoemulsification to stain the anterior capsule in patients with diabetic retinopathy. Methods. This was a single-center, prospective, randomized, individual cohort study. One eye in each patient with diabetic retinopathy underwent phacoemulsification without trypan blue capsule staining (control eye), while the other eye underwent phacoemulsification with trypan blue capsule staining (study eye). Both eyes underwent intraocular lens implantation. Preoperative and four-week postoperative quantitative and qualitative morphometric endothelial cell analyses of the cornea were performed using noncontact specular microscopy. Results. There were no significant differences in endothelial cell density (mean ± SD for the study group: 2506.74 ± 413.99 cells/mm2; mean ± SD for the control eyes: 2466.34 ± 369.12 cells/mm2; P=0.316) or endothelial cell density (CD) loss% (mean CD loss% was 7.23 ± 13.31 for the study eyes and 9.94 ± 9.36 for the control eyes; P=0.157) four weeks after the operation. Additionally, no significant differences were seen in the percentage of hexagonal cells, coefficient of variation, or corneal thickness between the two groups preoperatively and 4 weeks postoperatively. Conclusions. Direct administration of trypan blue into the anterior chamber for staining of the anterior capsule during cataract surgery did not result in any significant corneal endothelial changes on specular microscopy in patients with severe nonproliferative diabetic retinopathy or high-risk proliferative diabetic retinopathy at 4 weeks postoperatively. This trial is registered with NCT03755752.